Lipid Profile and Obese Related Genes of Rats, Potential Therapeutic Effects of Peganum Harmala /Zinc Oxide Nanoparticles - Abdelsattar , Mervat; Elseady, Youssef; Awadin, Walaa F.; Hendawy, Ahmed; Diab , Abd EL-Aziz A. (Journal of Advanced Veterinary Research, 2023)
The present study investigated the effects of methanolic extract of harmala nanoparticle (H/ZnONP) on the changes in serum lipid profiles, serum leptin levels and liver and kidney PPAR gene expression in high caloric diet (HCD) induced obese rats. After induction of obesity with HCD for one month to half numbers of rats. Non-obese group had three subgroups; G1: Control fed basal diets, G2: basal diets plus H/ZnONPs (200 mg/kg/day) and G3: basal diets plus H/ZnONPs (400 mg/kg/day). However, obese group was divided into three subgroups G4: HFD, G5: HFD+H/ZnONPs (200 mg/kg/day) and G6: HFD+ H/ZnONPs (400 mg/kg/day). After 4 weeks of treatment blood and tissue samples were collected and subjected to laboratory assay of lipid profile and leptin level in addition to expression of PPAR gene in liver and kidney. We also investigated the possible protective effect of H/ZnONP 200 and 400 mg/kg BW on liver and kidney histology. The obtained results demonstrated that H/ZnONP treatment to obese rats significantly decreased serum cholesterols, triglyceride, and LDL level while relative expression of PPAR gene in liver and kidney was significantly increased. Based on the obtained results we can concluded that H/ZnONP supplementation has a potent anti-obesity effect in rats by improving lipid profile, enhance expression of PPAR gene in liver and kidney and improve liver and kidney histology particularly the high dose.